A study on students' attitude and motivation in learning English as a second language / Nur Hazwani Mohd Zaini - Mohd Zaini, Nur Hazwani (2014)
Learning English language has become a challenge to students in Malaysia in learning the language well. Learners' attitude and motivation are identified to play essential roles to ensure that students are able to learn English language well because both factors contribute to students' desire in learning the language, as well as improving their achievement in the language. Thus, a study needs to be carried out to determine Form Five students' attitude and motivation in learning English language as a second language. A survey was carried out using a questionnaire distributed to fiftytwo average proficiency level students of Form Five in a secondary school in Shah Alam, Selangor. Interviews were also conducted with five students selected at random. In relation to RQ 1, this study was to identify students' attitude towards learning English as a second language. The study revealed that the students generally have positive attitudes in learning English language as a second language as the mean score for positive attitude is above 4.00 compared to the mean score obtained for negative attitude is below 3.00. RQ 2 was to identify the intrinsic motivation in learning English as a second language. The results revealed that students have strong desire to learn English due to intrinsic reasons such as for self-development and to be at ease with English speakers. In addition, RQ 3 of this study was to identify the extrinsic motivation in learning English as a second language. For the extrinsic motivation, students learn English language to get a good job and also do well in examination. RQ 4 was to identify other factors that motivate students in learning English as a second language. The finding indicated that obtaining good grade and passing examinations are the reasons given. RQ 5 was to identify language activities that motivate students in English classroom. The findings indicated that students prefer to learn English language through language activities. There are three suggested activities, such as Role Play, Chinese Whispering and Pretending to be Someone that can be used in the English classroom because it is fun and they can learn better through interactive activities. In order to get a better perspective of students' attitude and motivation in learning English language as a second language, it is recommended that a bigger pool of respondents from all levels of proficiency levels among Form Five students from a bigger number of secondary schools in Malaysia be carried out in the future to ensure that the results are applicable and can be generalized to a larger population.